Impact of alcohol consumption on atherosclerosis: a systematic review and meta-analysis - Song, Jiayuan; She, Jiuhua; Yin, Jinzhu; Hu, Sihan; Shi, Guijun; Chang, Liping (Frontiers in Nutrition, 2025)
IntroductionAtherosclerosis, a chronic vascular disease, impacts various arterial systems, such as the coronary, carotid, cerebral, renal, and peripheral arteries. Dietary factors, especially alcohol consumption, significantly contribute to the progression of atherosclerosis. However, systematic evaluations of alcohol’s impact on atherosclerosis are still limited. This study investigates the impact of alcohol consumption on atherosclerosis via meta-analysis and assesses the moderating effects of drinking frequency, gender, and other factors.MethodsBy December 2024, a comprehensive literature search was conducted across PubMed, Embase, Cochrane, and Web of Science databases. Studies evaluating the relationship between alcohol consumption and atherosclerosis were rigorously selected and assessed for quality. The study protocol was registered with the INPLASY database. Data extraction and statistical analysis were conducted using STATA 18.0 software. A total of 26 studies involving 326,513 patients across 10 countries were included. Considering that different biological mechanisms may regulate atherosclerosis in different arterial locations, we conducted subgroup analyses to explore differences in country, study type, arterial site, diagnostic criteria, type of alcohol, and gender.ResultThe results show that the overall analysis did not show a significant promoting effect of alcohol consumption on the development of atherosclerosis (OR = 0.91, 95% CI 0.79–1.05). Subgroup analyses revealed several important trends. Alcohol consumption may increase the risk of atherosclerosis in specific countries (Japan, South Korea, Brazil, and Denmark), types of studies (cohort and case–control studies), arterial locations (coronary arteries), and diagnostic criteria (clinical diagnosis and computed tomography). Interestingly, we found that alcohol consumption may increase the risk of atherosclerosis in women. Furthermore, varying levels of alcohol consumption appear to result in differing risks of the disease.ConclusionThe impact of alcohol consumption on atherosclerosis is not singular and may interact with multiple factors, including environmental factors, lesion location, and individual characteristics.Systematic review registrationhttps://inplasy.com/inplasy-2025-1-0031/, INPLASY202510031.